Advanced Handbook of Systemic Lupus Erythematosus - Arnaud, Laurent (Springer International Publishing, 2018)
This book will provide an introduction to the epidemiology, etiology and pathogenesis of the condition while also exploring the classification, diagnosis, and current and emerging therapies for systemic lupus erythematosus. Systemic lupus erythematosus is an autoimmune disease in which the body's immune system mistakenly attacks healthy tissue. It can affect the skin, joints, kidneys, brain, and other organs. The underlying cause of the disease is not fully known, and SLE is much more common in women than in men. It may occur at any age but most often occurs in people between 10 and 50 years of age. This is the second Adis title from Ronald F van Vollenhoven, who previously authored Biologics for the Treatment of Rheumatoid Arthritis.